2015
DOI: 10.1515/mgrsd-2015-0025
|View full text |Cite
|
Sign up to set email alerts
|

Livelihood assessment in district 1 of Medellin – Colombia

Abstract: The livelihood approach aims at the analysis, understanding and restrictions that the poorest people have to face in order to recover from difficult situations. The Department for International Development model is applied to an urban zone with the purpose of making an assessment of the livelihood of the district 'la Comuna 1' in Medellin, Colombia, which has been recognised as the poorest and one of the most dangerous districts of the city. The case study presents both a quantitative analysis (macro) and qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
0
5
0
2
Order By: Relevance
“…In relation to hypothesis H4, results of this study indicated that there is a relationship between social asset and livelihood outcomes as the path analysis suggested that the hypothesis is supported positively. The finding is not surprising as previous empirical studies opined that there is a correlation between social asset and livelihood outcomes (Oumer & De Neergaard, 2011;Alfonso et al, 2015;Islam, & Yew, 2013;Thi et al, 2013).…”
Section: Discussionmentioning
confidence: 59%
“…In relation to hypothesis H4, results of this study indicated that there is a relationship between social asset and livelihood outcomes as the path analysis suggested that the hypothesis is supported positively. The finding is not surprising as previous empirical studies opined that there is a correlation between social asset and livelihood outcomes (Oumer & De Neergaard, 2011;Alfonso et al, 2015;Islam, & Yew, 2013;Thi et al, 2013).…”
Section: Discussionmentioning
confidence: 59%
“…The expert-criteria states that the variables of those indicators associated with social dimensions such as poverty and hunger prevail over environmental dimensions since the Aburrá Valley belongs to a developing country, where the priority is often given to this type of dimension. This premise is supported by the studies of Boggia and Cortina (2010); Bečić et al (2012); Abou-Ali and Abdelfattah (2013); Serna Mendoza et al (2015), who indicate that indicators available in developing countries are mainly focused on socioeconomic dimensions. However, in recent years, Colombia has presented advances in health and education and reductions in mortality rates, reflecting a high rate of human development (UNDP 2016).…”
Section: Data and Indicator Descriptionmentioning
confidence: 83%
“…On the other hand, sustainability studies at different territorial levels are increasing, including subnational regions, cities, municipalities, micro-regions, and even neighborhood groups (Londoño and Cruz 2019;Moreno et al 2014;Moreno and Fidélis 2015;Schneider et al 2018;Subramanian et al 2021), showing the need to assess sustainable development in the different planning and management units (Serna et al 2015). A sign of this is the work by Boggia and Cortina (2010) that assessed sustainable development in 92 municipalities in Umbria, a region in central Italy; Moreno-Pires and Fidélis (2012) presented a similar study in the municipality of Palmela, Portugal; and Lee (2014) did the same for the region of Chiayi, Taiwan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although initial efforts to advance towards sustainable development resulting from the Rio Summit had an international focus, action has been increasingly focused at a local level (Kondyli, 2010; Tanguay et al, 2010). In actual fact, different studies have been carried out on sustainable development which have focused on cities, municipalities and even neighbourhoods (Mascarenhas, Nunes, & Ramos, 2015; Moreno, Fidélis, & Ramos, 2014; Moreno Pires & Fidélis, 2012, 2015; Roca & Oliveira-Roca, 2007; Serna, Czerny, Londoño, & Vélez, 2015; Vélez & Londoño, 2016). This study is carried out within such an approach, since it aims to understand the problems associated with sustainability in the municipality of San Miguel de Achiutla, located in the region of Mixteca Alta in Oaxaca, Mexico.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%